Mudança do sistema informatizado de orçamentação prévia utilizado na Unidade de Negócios Refinaria Duque de Caxias para a contratação dos serviços de caldeiraria nas paradas de manutenção das unidades de processamento - Pereira, Marcus dos Santos (2007)
This work aims to analyze changes in the system of budgeting prior services that are made during the maintenance of the processing units at Duque de Caxias Refinery of PETROBRAS. In order to reach this objective, it is shown, initially, a brief history of the legislation that directed the hiring of services in PETROBRAS under the aspect of the requirement of a prior budgeting and contextualization of the budgeting in the process of hiring the Duque de Caxias Refinery. Then, the variables that affect the budget of services under consideration were studied, inc1uding those related to taxes, and the systems (current and former) to calculate the final prices of the services. It is conc1uded that the new system has brought greater reliability to the values found, but much remains to be done in this area, since the determination of rates productivity of labor to the most detailed study of materiaIs related to labor legislation and taxo